Competing for Securities Underwriting Mandates: Banking Relationships and Analyst Recommendations - LJUNGQVIST, ALEXANDER; MARSTON, FELICIA; WILHELM, WILLIAM J. (Journal of Finance, 2006)
ABSTRACT We investigate whether analyst behavior influenced banks' likelihood of winning underwriting mandates for a sample of 16,625 U.S. debt and equity offerings in 1993–2002. We control for the strength of the issuer's investment banking relationships with potential competitors for the mandate, prior lending relationships, and the endogeneity of analyst behavior and the bank's decision to provide analyst coverage. Although analyst behavior was influenced by economic incentives, we find no evidence that aggressive analyst behavior increased their bank's probability of winning an underwriting mandate. The main determinant of the lead‐bank choice is the strength of prior underwriting and lending relationships.